2010
DOI: 10.4049/jimmunol.0903301
|View full text |Cite
|
Sign up to set email alerts
|

Improving Survival Rates in Two Models of Spontaneous Postoperative Metastasis in Mice by Combined Administration of a β-Adrenergic Antagonist and a Cyclooxygenase-2 Inhibitor

Abstract: Clinical practice does not consider perioperative paracrine and neuroendocrine stress responses as risk factors for cancer recurrence, although recent animal studies provided supportive evidence. Suggested mechanisms include the effects of stress-hormones on tumor cells and on host physiology. In this study, in mice undergoing primary tumor excision, we tested the survival-enhancing potential of perioperative blockade of catecholamines and prostaglandins, and studied potential mediating mechanisms. C57BL/6J mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
187
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(198 citation statements)
references
References 55 publications
7
187
0
4
Order By: Relevance
“…Interestingly, in many cancers, metastases are more likely to form only after the primary tumor is removed. This is caused by increased dissemination of tumor cells during the removal of the primary tumor (20), decreased levels of anti-angiogenic factors, local and systemic increases in proangiogenic and growth factors (e.g., VEGF) (21), blood loss (22), and the suppression of cell- mediated immunity (following the surgery) (23,24). Also, the primary tumor is known to secrete immunosuppressive factors such as PGE 2 , IL-10 and TGF-b, which increase the likelihood of tumor cells to stay close to the initial mass of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in many cancers, metastases are more likely to form only after the primary tumor is removed. This is caused by increased dissemination of tumor cells during the removal of the primary tumor (20), decreased levels of anti-angiogenic factors, local and systemic increases in proangiogenic and growth factors (e.g., VEGF) (21), blood loss (22), and the suppression of cell- mediated immunity (following the surgery) (23,24). Also, the primary tumor is known to secrete immunosuppressive factors such as PGE 2 , IL-10 and TGF-b, which increase the likelihood of tumor cells to stay close to the initial mass of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have demonstrated that β-adrenergic signaling can regulate multiple fundamental biological processes underlying the progression and metastasis of tumors, including the promotion of inflammation [72][73][74], angiogenesis [75][76][77][78], migration [79], invasion [80,81] and resistance to programmed cell death [82][83][84][85]. Some evidence suggests that the stimulation of β-adrenergic signaling can also inhibit DNA damage repair and the cellular immune response [86,87] and promote surgery-induced metastasis [88,89]. Figure 5 β-adrenergic signaling modulates multiple cellular processes in tumor progression and metastasis.…”
Section: β-Adrenergic Signalingmentioning
confidence: 99%
“…Propranolol, a non-selective b-adrenergic blocking agent, is used predominantly for the treatment for hypertension, cardiac arrhythmias, coronary artery disease, thyrotoxicosis, migraine headache, and a number of other conditions such as psychiatric diseases (Emilien and Maloteaux 1998;Frohlich 1977;Featherstone 1983;Lee et al 1982). In recent years, the data obtained from meta-analysis and in vitro and in vivo experimental studies showed that beta-receptor antagonists inhibit tumor proliferation and metastasis in breast, stomach, skin, and colon cancers (Masur et al 2001;Benjamin et al 2010;Slotkin et al 2000;Glasner et al 2010;Benish et al 2008;Algazi et al 2004;Park et al 1995). In vitro, the antiangiogenic biological activity of propranolol was also shown to inhibit human brain microvascular endothelial cell tubulogenesis (Annabi et al 2009).…”
Section: Introductionmentioning
confidence: 99%